Effect of male child preference on the decision making of women in choosing contraception - Pathak, Varuna; Arya, Ruchika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pressures resulting from unrestrained human population growth put demands on the natural world that can overwhelm any efforts to achieve a sustainable future. If we are to halt the destruction of our environment, we must accept limits to that growth. In this hospital based study, we aim to study the factors that influence the choice of contraception. Purpose of this study is to analyze the contraceptive behavior which is a product of many determinants such as age, religion, education, parity, fertility, child care support, economic and social circumstances, motivation, communication and the perception of reliability and safety of a chosen method thereby ensuring better health for the mother and better care and upbringing of children. Methods: The present study entitled effect of male child preference on the decision making of women in choosing contraception is a cross sectional study carried out on 700 subjects in Department of Obstetrics and Gynaecology, Sultania Zanana Hospital, Gandhi Medical College, Bhopal. Study population includes women of reproductive age group who came to seek contraceptive advice from family planning OPD of the hospital. Results: Subjects having 2 male children preferred permanent method of contraception (66%) as compared to subjects having 2 female children (7.93%), this result is statistically significant(p<0.05) showing a strong preference for male child in Indian society. Conclusions: The results indicated that a woman’s desire to limit family size with preferred sex composition of children, coupled with her autonomy and the socio cultural context, are the major determinants of contraceptive method choices.